A Non-English Students' Strategies in Learning Technical Vocabularies - Wahyuni, Sri; Akib, Erwin; Mannong, Andi Bulkis Maghfirah (FKIP Unismuh Makassar, 2024)
This research aimed to finding out the strategies that usually used in learning technical vocabularies by Non-English students’. This research applied the Descriptive Qualitative Method, which took 2 months period of it for the data collection by using interview. The research involved ten students’ from Faculty Economic and Business Universitas Muhammadiyah Makassar as the participants. The scope of the study is tend to analyze the strategies used by Non-English students’ in learning a foreign language, in this case English. A result of this research showed that the strategies that usually used in learning technical vocabularies by Non-English students’ most of the students’ used direct strategies, namely memory strategies, cognitive strategies and compensation strategies. And the students’ also used indirect strategies, namely metacognitive strategies, affective strategies and social strategies. Based on the data obtained, the researcher concluded that the students’ used both strategies in learning technical vocabularies.